In vivo protection of diisopropylphosphorofluoridate (DFP) poisoning by three bis-quaternary 2 -(hydroxyimino) -N -(pyridin-3-yl) acetamide derivatives in Swiss mice - Kumar, P.; Swami, D.; Karade, H. N.; Acharya, J.; Jatav, P. C.; Kumar, A.; Meena, M. K. (Cellular and Molecular Biology, 2014)
This study reports efficacy of three bis pyridinium derivatives of 2-(hydroxyimino)- N-(pyridine-3-yl) acetamide in terms of survival, reactivation of brain and serum acetylcholinesterase (AChE) activity in diisopropylphosphorofluoridate (DFP) intoxicated Swiss albino male mice. LD50 of DFP (3.9 mg/kg, s.c.) and new oximes, HNK-102, HNK-106, HNK-111, (282.8, 35.0 and 35.0 mg/kg respectively, i.m.) was determined. Various doses of DFP and oximes as treatment doses with atropine (10 mg/kg, i.p.) were used to determine protection index (PI). For time dependent maximum AChE inhibition, two doses of DFP (0.20 and 2.0 LD50) were chosen. At optimized time i.e. Sixty minutes, IC50 value was calculated as 0.249 and 0.017 LD50 of brain and serum AChE, respectively. Shift of DFP induced brain AChE IC50 curves to right was observed at 0.20 LD50 treatment dose of oximes with respect to 2-PAM. These findings propose that new HNK series of oximes are effective antidote, compared to that of 2-PAM in vivo.